2015
DOI: 10.2147/oaap.s83190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation of betaine hydrochloride on physiological performances of broilers exposed to thermal stress

Abstract: Background: Betaine has the potential to spare methionine and choline as methyl-group donors, and is thought to improve broiler performance under conditions of stress. An experiment was conducted to ascertain the effects of supplemental betaine on performances and physiological responses of broilers exposed continuously to thermal stress. Materials and methods: Male broilers (n=128, divided into four groups, with eight replicate cages in a group) received diets containing suboptimal levels of methionine and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
4
8
0
Order By: Relevance
“…The current study demonstrated the role of dietary betaine in increasing serum TAG and TC levels of quails fed diets containing restricted and low ME levels compared with that of birds fed betaine-non-supplemented diets containing optimum and restricted ME levels ( Table 3 ). These results were consistent with previous work [ 18 ] stated the same role of dietary betaine in broilers at higher (2.0 g/kg), and lower (1.3 g/kg) levels of supplementation. The decreased levels of serum TAG might be attributed to the activity of hormone-sensitive lipase in response to dietary betaine.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The current study demonstrated the role of dietary betaine in increasing serum TAG and TC levels of quails fed diets containing restricted and low ME levels compared with that of birds fed betaine-non-supplemented diets containing optimum and restricted ME levels ( Table 3 ). These results were consistent with previous work [ 18 ] stated the same role of dietary betaine in broilers at higher (2.0 g/kg), and lower (1.3 g/kg) levels of supplementation. The decreased levels of serum TAG might be attributed to the activity of hormone-sensitive lipase in response to dietary betaine.…”
Section: Discussionsupporting
confidence: 94%
“…Although the dietary ME levels were suboptimal (restricted and low ME) in either without or with betaine supplementation, respectively, production performance of Japanese quail has not been negatively impacted as shown in Table 2 . Similar study [ 18 ] reported that dietary betaine with suboptimal levels of dietary ME did not induce a significant changes on growth performance of broilers chickens. However, other studies [ 4 , 34 ] demonstrated that, dietary betaine had a positive influence on poultry performance.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Chand et al [14] found that dietary supplementation of 1.5% and 2% betaine increased the feed intake and BWG and reduced the FCR of fast-growing broilers exposed to heat stress. Similar findings have been reported in the studies of Sakomura et al [16] and Singh et al [24], who observed a significant increase in feed intake and BWG of heat stressed Cobb broilers fed with diet contained betaine. However, the studies related to the effects of betaine on indigenous slow-growing broilers are very scarce.…”
Section: Discussionsupporting
confidence: 91%